PENGARUH LATIHAN KONDISI FISIK TERHADAP KEMAMPUAN MELEMPAR PADA ATLET BOCCE DI SMALB NEGERI PEMBINA MEDAN - roby octavianus malau (Jurnal Kesehatan dan Olahraga, 2020)
ROBY OCTAVIANUS MALAU. "The Effect of Physical Condition Exercise on Throwing Ability in Bocce Athletes in the State Guiding Board of SMALB Medan". (Supervisor: Puji Ratno S.Si.M.Pd) Thesis Medan: Bachelor Program in the Faculty of Sport Science Medan State University 2020. This study was conducted to determine whether physical condition exercises affect the athlete at the SMALB Negeri Pembina Medan Field, especially in the ability to throw a bocce ball. This physical condition exercise is said to be successful if the data from the post-test result is better than the data from the pre-test result. The purpose of this study was to determine the effect of physical condition training on the ability to throw a bocce athlete in State High School of Pembina Medan.This study uses the Pretest-Posttest Design One Group Experiment method, from the results of pre-test data processing, an average value of 172.5 and post-test 76 is obtained. Thus the results of the post-test toss are better than the pre-test. Thus obtained Tcount> Ttable is 4.17> 2.015. Based on these results, H0 was rejected and Ha was accepted, which means "Significantly needed from the physical training released on the leaked athlete at Medan State Foster High School".Keywords: Bocce, throwing ability, physical condition training, mental retardation